2018
DOI: 10.1002/pon.4678
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of caregiver burden and related factors in family caregivers of patients with lung cancer

Abstract: The results support the existing and different types of subtrajectories of the FC's burden. Health care professionals should provide care based on those differences. Further research to test interventions which integrate those important factors related to FC's burden, particularly FC's self-efficacy, is strongly suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 38 publications
(80 reference statements)
9
35
0
Order By: Relevance
“…Regarding the year of publication, 36 out of 62 articles were published in 2017 and 28 in 2018. Countries where the respective studies were conducted were the USA/Canada ( n = 23) [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31], Scandinavia ( n = 7) [32,33,34,35,36,37,38], UK ( n = 4) [39,40,41,42], Germany ( n = 4) [43,44,45,46], Southern Europe (Italy, Portugal, Spain; n = 8) [47,48,49,50,51,52,53,54], East Asia (Japan, China, Korea, Taiwan; n = 4) [55,56,57,58,59,60], Australia/New Zealand ( n = 4) [61,62,63,64], other ( n = 4) [65,66,67,68], and multinational ( n = 2) [69,70].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the year of publication, 36 out of 62 articles were published in 2017 and 28 in 2018. Countries where the respective studies were conducted were the USA/Canada ( n = 23) [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31], Scandinavia ( n = 7) [32,33,34,35,36,37,38], UK ( n = 4) [39,40,41,42], Germany ( n = 4) [43,44,45,46], Southern Europe (Italy, Portugal, Spain; n = 8) [47,48,49,50,51,52,53,54], East Asia (Japan, China, Korea, Taiwan; n = 4) [55,56,57,58,59,60], Australia/New Zealand ( n = 4) [61,62,63,64], other ( n = 4) [65,66,67,68], and multinational ( n = 2) [69,70].…”
Section: Resultsmentioning
confidence: 99%
“…Forty-seven studies reported on relatives of advanced cancer patient’s [9,10,11,13,15,16,17,18,19,20,21,22,23,24,26,27,28,29,30,31,32,34,36,37,38,39,42,43,44,46,47,48,49,50,51,52,53,55,56,57,58,59,60,61,65,66,67] and 15 studies included relatives of mixed patient samples [12,14,25,33,35,40,41,45,54,62,63,64,68,69,70]. The environment in which the patient received palliative or hospice care were home care in 18 studies [10,14,25,26,27,30,3...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Videoconference technology may alleviate some of this stress by allowing DCGs to be “present” for the patients' appointments without worrying about the logistics of traveling to be with them in person. In addition, individualized coaching from trained professionals familiar with the unique needs of DCGs may enhance their sense of self‐efficacy as a caregiver, which has been shown to decrease burden, distress, and anxiety (Kershaw et al, ; Lee et al, ). We hypothesize that for those involved in the videoconference sessions, seeing the patient, meeting the oncologist, and being part of the discussion will lessen the burden of caring from a distance, particularly when paired with monthly coaching sessions to help them navigate the health care system.…”
Section: Discussionmentioning
confidence: 99%